Penyuluhan Dan Praktik Perilaku Hidup Bersih Dan Sehat (PHBS) Pada Komunitas Adat Terpencil (KAT) Di Desa Bukit Suban Kecamatan Air Hitam Kabupaten Sarolangun - Rumita Ena Sari; Guspianto Guspianto; Evy Wisudariani (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2019)
Health problems in KAT are things that cannot be ignored by the government because their existence cannot be denied. As many as 1500 people of the Anak Dalam Tribe (SAD) / KAT inhabit the Bukit Duabelas National Park area and 450 inhabitants in the Bukit Tigapuluh Buffer area. Based on the needs of the community in KAT which are still low in knowledge and concern for health, it is necessary to provide counseling about PHBS, which is expected to be able to increase awareness so as to increase the degree of public health, especially in remote indigenous communities. Community service is carried out by stages of meeting with stakeholders and health workers, conducting PHBS counseling, conducting demonstrations on how to wash hands properly and brushing their teeth and conducting monitoring and evaluation of implementation. Increased understanding and awareness of the community at Bukit Suban Air Hitam on efforts to improve health status and be able to practice clean and healthy living behaviors in everyday life, especially in terms of washing hands with soap and how to brush teeth properly.